2011
DOI: 10.1016/j.neulet.2011.03.068
|View full text |Cite
|
Sign up to set email alerts
|

Gene and protein analysis of brain derived neurotrophic factor expression in relation to neurological recovery induced by an enriched environment in a rat stroke model

Abstract: Although an enriched environment enhances functional recovery after ischemic stroke, the mechanism underlying this effect remains unclear. We previously reported that brain derived neurotrophic factor (BDNF) gene expression decreased in rats housed in an enriched environment for 4 weeks compared to those housed in a standard cage for the same period. To further clarify the relationship between the decrease in BDNF and functional recovery, we investigated the effects of differential 2-week housing conditions on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 20 publications
(29 reference statements)
0
15
0
2
Order By: Relevance
“…Enhancement of BDNF production after stroke, mainly attributable to perilesional neurons but also to microglia [28], has been suggested as a brain compensatory mechanism to prevent excessive neuronal death [29]. However, several studies have concluded that BDNF is not involved in post-stroke functional recovery [30,31]. The most likely explanation for this outcome is the incapacity of BDNF to trigger appropriate neurotrophic signalling after stroke due to a pathological imbalance of TrkB receptor isoforms.…”
Section: Defective Expression and Stability Of Bdnf And Trkb In Nementioning
confidence: 99%
“…Enhancement of BDNF production after stroke, mainly attributable to perilesional neurons but also to microglia [28], has been suggested as a brain compensatory mechanism to prevent excessive neuronal death [29]. However, several studies have concluded that BDNF is not involved in post-stroke functional recovery [30,31]. The most likely explanation for this outcome is the incapacity of BDNF to trigger appropriate neurotrophic signalling after stroke due to a pathological imbalance of TrkB receptor isoforms.…”
Section: Defective Expression and Stability Of Bdnf And Trkb In Nementioning
confidence: 99%
“…Poststroke exercise and EE also increase expression of growth-associated proteins such as growth-associated protein 43 [49], microtubule-associated protein 2 [44], and netrin (along with the associated deleted in colorectal cancer receptor) [50], as well as markers of synaptogenesis [46,51,52]. Such proteins are involved in axonal sprouting, dendritic complexity, and spine growth [4], phenomena occurring in the peri-and contralesional cortex of functionally recovered animals [14,53].…”
Section: How Do Exercise and Enrichment Enhance Plasticity And Recovery?mentioning
confidence: 99%
“…A permanent BDNF decrease is found in the infarct core, while a long-lasting upregulation, proposed to be a neuroprotective mechanism, takes place in the penumbra (Ferrer et al, 2001;Madinier et al, 2013). However, other studies rejected BDNF involvement in post-stroke recovery (Hirata et al, 2011), a likely explanation being pathological downregulation of BDNF receptors. Three independent mechanisms induced by excitotoxicity act on TrkB: (i) An inversion of mRNA ratios disfavors TrkB-FL expression over TrkB-T1 (Gomes et al, 2012;Vidaurre et al, 2012); (ii) TrkB-FL cleavage by Ca 2+dependent calpain generates a truncated receptor similar to TrkB-T1 (Gomes et al, 2012;Vidaurre et al, 2012); and (iii) regulated intramembrane proteolysis (RIP) of both isoforms by metalloproteinase/c-secretase action sheds identical ectodomains acting as BDNF scavengers (Tejeda et al, 2016).…”
Section: Introductionmentioning
confidence: 99%